USING ENGLISH SONG TO IMPROVE STUDENTS’ VOCABULARY - Sitti Nurjannah; Muthmainnah Mursidin; Nurul Azizah (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
This research was carried out at SMPN 25 Makassar, in order to perform quantitative research, this research utilized a control class and an experimental class. Additionally, a vocabulary exam and one questionnaire were utilized. The sample for this study consists of seventy students, the seventh grade pre-test at SMPN 25 Makassar, the results demonstrated that there was an increase in the vocabulary of the students. The mean pre-test score in the experimental class was 57.8 and the mean score in the control class was 73.1. On the other hand, the average post-test score for the test in the control class was 73.1, and the experimental class had 58.8 and the mean score in the control class was 69.3. After receiving treatment, there was a substantial difference between the scores obtained on the pre-test and the post-test. The researchers are able to draw the conclusion that students have a strong interest in the English song learning technique because the results of the questionnaire data showed the effectiveness in improving their English vocabulary through the use of English song.